2016
DOI: 10.1038/npp.2016.138
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ablation of GIRK Channels in Dopamine Neurons Alters Behavioral Effects of Cocaine in Mice

Abstract: The increase in dopamine (DA) neurotransmission stimulated by in vivo cocaine exposure is tempered by G protein-dependent inhibitory feedback mechanisms in DA neurons of the ventral tegmental area (VTA). G protein-gated inwardly rectifying K + (GIRK/Kir3) channels mediate the direct inhibitory effect of GABA B receptor (GABA B R) and D 2 DA receptor (D 2 R) activation in VTA DA neurons. Here we examined the effect of the DA neuron-specific loss of GIRK channels on D 2 R-dependent regulation of VTA DA neuron ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 42 publications
6
42
1
Order By: Relevance
“…In cocaine self-administration experiments, GIRK2 DA KO mice exhibit an increased number of cocaine infusions, particularly at low doses, and an increase in total intake of cocaine [76]. Interestingly, conditioned place preference with cocaine is unaffected by GIRK2 knockout [76]. Overall, these conditional GIRK2 knockout experiments support the view that expression of GIRK channels in VTA DA neurons plays an important modulatory role in the behavioral responses to cocaine and morphine.…”
Section: Effects Of Girk Knockouts On Addictive Behaviorsmentioning
confidence: 84%
See 1 more Smart Citation
“…In cocaine self-administration experiments, GIRK2 DA KO mice exhibit an increased number of cocaine infusions, particularly at low doses, and an increase in total intake of cocaine [76]. Interestingly, conditioned place preference with cocaine is unaffected by GIRK2 knockout [76]. Overall, these conditional GIRK2 knockout experiments support the view that expression of GIRK channels in VTA DA neurons plays an important modulatory role in the behavioral responses to cocaine and morphine.…”
Section: Effects Of Girk Knockouts On Addictive Behaviorsmentioning
confidence: 84%
“…Studies with a cell-type specific ablation of GIRK2 in DA neurons (DAT-Cre +/− : Girk2 fl/fl or GIRK2 DA KO mice) reveal enhanced acute and chronic locomotor response to cocaine [76]. In cocaine self-administration experiments, GIRK2 DA KO mice exhibit an increased number of cocaine infusions, particularly at low doses, and an increase in total intake of cocaine [76]. Interestingly, conditioned place preference with cocaine is unaffected by GIRK2 knockout [76].…”
Section: Effects Of Girk Knockouts On Addictive Behaviorsmentioning
confidence: 99%
“…Work with knockout mice suggests that behavioral sensitivity to cocaine is inversely proportional to the strength of GIRKdependent signaling in DA neurons. Girk2 Ϫ / Ϫ mice exhibit increased locomotor responses to cocaine and morphine (Arora et al, 2010;Kotecki et al, 2015) and altered cocaine self-administration (Morgan et al, 2003), as do mice lacking GIRK channels in DA neurons (DATCre(ϩ):Girk2 fl/fl mice) (Kotecki et al, 2015;McCall et al, 2017). However, Girk2 Ϫ / Ϫ mice exhibit an array of other behavioral phenotypes (Signorini et al, 1997;Blednov et al, 2001Blednov et al, , 2003Marker et al, 2004Marker et al, , 2005Costa et al, 2005;Pravetoni and Wickman, 2008), as well as adaptations in excitatory and inhibitory neurotransmission in multiple rewardassociated neuron populations (Arora et al, 2010;Hearing et al, 2013), making it challenging to attribute changes in cocainerelated behavior to a specific population.…”
Section: Introductionmentioning
confidence: 99%
“…Inwardly rectifying potassium channels are activated by neurotransmitters and hormones as well as by other messengers such as kinases and G-proteins (Dascal, 1997). The G protein-activated potassium (GIRK) channels can be directly activated by ethanol (Aryal et al , 2009) and have been found to play a role in drug addiction (Herman et al , 2015; McCall et al , 2016; Munoz et al , 2016; Rifkin et al , 2017). Here we show that ethanol-induced CPP increases the excitability of vBNST neurons by potentially blocking inwardly-rectifying potassium channels.…”
Section: Discussionmentioning
confidence: 99%